Studi Perbandingan Konflik Pers Indonesia dan Pers Malaysia dalam Konteks Nationality of Press dan Neighborâ€™s Press - Mauliansyah, Fiandy (Universitas Teuku Umar, 2017)
This paper aim to examine on a comparison between press freedom in Indonesia and Malaysia in proclaiming their relationship. This study is expected to explain more about the difference that the author seems to differences over the rationality and public opinion. In this study, it was found that freedom of the press in the context of â€œneighboring countriesâ€ on the one side can be a fire in the hull that is tangible to the bilateral conflict so that each lost principle of balancing of the press. But on the other side, freedom of the press, however â€“ more realiable in rationality and acceptance of public opinion, the similarities and differences are quite acceptable.Keywords: Freedom of the Press. Neighborâ€™s Press. Rasionality and Public Opinion